Margin Requirements, Volatility, and the Transitory Component of Stock Prices - Hardouvelis, Gikas A. (American Economic Review, 1990)
Official margin requirements in the U.S. stock market were established in October 1934 to limit the amount of credit available for the purpose of buying stocks. Since then, higher or rising margin requirements are associated with lower stock price volatility, lower excess volatility, and smaller deviations of stock prices from their fundamental values. The results hold throughout the post-1934 period and are not very sensitive to the exclusion of the turbulent depression years from the sample. Thus margin requirements seem to be an effective policy tool in curbing destabilizing speculation.